Die Social Media Matrix - Orientierung fur̈ die Versicherungsbranche - Michaele Völler (Technische Hochschule Köln, Institut für Versicherungswesen (ivwKöln), 2012)
Ziel dieser Arbeit ist es, Versicherungsunternehmen eine Orientierungshilfe in Social Media zu geben. Hierzu wird eine Kategorisierung der vielfal̈tigen Web 2.0-Dienste geboten, die Social Media Matrix, die fun̈f wesentliche Social Media-Kategorien unterscheidet und hinsichtlich ihrer Eignung fur̈ Versicherungsunternehmen bewertet. – – This paper offers a guideline to social media to insurance companies. For this purpose the varied web 2.0 services are classified by the "Social Media Matrix" which differentiates between five main categories. Moreover the different web formats are evaluated concerning their suitability for insurance companies.
urn:nbn:de:hbz:832-cos-140
Keywords: 330; World Wide Web 2.0; Soziale Software; Versicherungswirtschaft